Assessment of the Use of Epicarp and Mesocarp of Green Coconut for Removal of Fluoride Ions in Aqueous Solution - César Augusto Canciam; Nehemias Curvelo Pereira (International Journal of Chemical Engineering)
Fruit consumption and processing result in considerable volumes of residual biomass. Transformation of this biomass into biosorbents offers an alternative for its reuse and disposal. As the green coconut shell is a waste often discarded in landfills and dumps, generating gases and leachate, two biosorbents were developed from the epicarp and mesocarp of green coconut to adsorb fluoride ions in aqueous solution. The kinetic experiments showed that sorption of fluoride ions reached equilibrium at 300 min for both epicarp and mesocarp at temperatures of 25°C, 35°C, and 45°C. The removal efficiency of fluoride ions varied from 66.25% (at 25°C) to 77.50% (at 45°C) for the epicarp and from 90% (at 25°C) to 97.50% (at 45°C) for the mesocarp. The thermodynamic parameters of the adsorption process showed that adsorption is a spontaneous, endothermic process for both biosorbents. The adsorption was classified as chemical, with the Langmuir isotherm model best suited to the adsorption isotherms data.